Identification of FAME (Fatty Acid Methyl Esters) Products from the Interesterification Reaction of Palm Oil with Methyl Ester Co-solvent - Elvianto Dwi Daryono; Dwi Ana Anggorowati (Universitas Islam Raden Rahmat, Malang, 2025)
Methyl ester co-solvent will accelerate the reaction without the need for a separation stage at the end of the reaction. The study aims to determine the effect of FAME co-solvent concentration and time of reaction on the methyl ester produced in the interesterification reaction of palm oil into biodiesel with methyl ester co-solvent. The weight of the oil used was 250 g, the mole ratio of oil: methyl acetate = 1:6, the temperature was 60oC, the concentration of the co-solvent (0 - 20%), the reaction time (30-90 min), the catalyst KOH 1% and the stirring speed was 800 rpm. The oil, methyl acetate and catalyst were placed in a three-necked flask and the reaction was carried out according to the operating conditions. The optimum conditions were obtained in the palm oil interesterification process with a FAME co-solvent concentration of 20% and a time of reaction of 30 min with a methyl ester concentration of 61,413 mg/L and an acid value of 0.28 mg KOH/g which met SNI 7182-2015. The research revealed a biodiesel production process with fewer steps, faster reaction times, higher yields, and product physical properties that meet standards. It is hoped that this process can be implemented at a pilot plant scale, bringing the selling price of biodiesel closer to that of diesel fuel.